Genome-wide identification and analysis of Oleosin gene family in four cotton species and its involvement in oil accumulation and germination - Yanchao Yuan (BMC, 2021)
Abstract Background Cotton is not only a major textile fiber crop but also a vital oilseed, industrial, and forage crop. Oleosins are the structural proteins of oil bodies, influencing their size and the oil content in seeds. In addition, the degradation of oleosins is involved in the mobilization of lipid and oil bodies during seed germination. However, comprehensive identification and the systematic analysis of the Oleosin gene (OLEOs) family have not been conducted in cotton. Results An in-depth analysis has enabled us to identify 25 and 24 OLEOs in tetraploid cotton species G. hirsutum and G. barbadense, respectively, while 12 and 13 OLEOs were identified in diploid species G. arboreum and G. raimondii, respectively. The 74 OLEOs were further clustered into three lineages according to the phylogenetic tree. Synteny analysis revealed that most of the OLEOs were conserved and that WGD or segmental duplications might drive their expansion. The transmembrane helices in GhOLEO proteins were predicted, and three transmembrane models were summarized, in which two were newly proposed. A total of 24 candidate miRNAs targeting GhOLEOs were predicted. Three highly expressed oil-related OLEOs, GH_A07G0501 (SL), GH_D10G0941 (SH), and GH_D01G1686 (U), were cloned, and their subcellular localization and function were analyzed. Their overexpression in Arabidopsis increased seed oil content and decreased seed germination rates. Conclusion We identified OLEO gene family in four cotton species and performed comparative analyses of their relationships, conserved structure, synteny, and gene duplication. The subcellular localization and function of three highly expressed oil-related OLEOs were detected. These results lay the foundation for further functional characterization of OLEOs and improving seed oil content.